Optimizing Disbursement of Zakat Funds for Asnaf Entrepreneurs - Rosalina, Hamdah; Bahri, Efri Syamsul (ITQAN: Journal of Islamic Economics, Management, and Finance, 2022)
Zakat is a pillar of Islam that must be fulfilled by Muslims who have met the requirements of nisab. Zakat collected, then channeled to mustahiq. One of the effective zakat distribution programs for poverty alleviation is the asnaf entrepreneur's program. This study aims to describe the sharia provisions and regulations about Asnaf Entrepreneurs in the context of Indonesia. This study also identifies the zakat management entity that runs the asnaf entrepreneurs program in Indonesia. This study is a study of literature obtained from various references. The analysis was performed with a descriptive approach and content analysis. The results of the study found that the sharia provisions of Asnaf Entrepreneurs are permissible. It has been exemplified by Rasulullah SAW. While the regulatory provisions on asnaf entrepreneurs are in Law No. 23 of 2011, and Regulation of the Minister of Religion No. 52 of 2014. This study also found some examples of zakat management entities that have optimized zakat funds for Asnaf Entrepreneurs including Zakat Pulau Penang (ZPP), Badan Amil Zakat Nasional (known as Baznas), BAZNAS Riau Province, Perbadanan Baitulmal Negeri Sembilan, Lembaga Zakat State of Kedah Darul Aman, Baitul Maal Hidayatullah (BMH), and DT Peduli. This study recommends the need for institutions that specifically supervise the Asnaf Entrepreneurs program globally. It is to optimize the contribution of zakat in poverty alleviation mustahiq. However, the asnaf Entrepreneurs program has contributed to poverty alleviation in Indonesia and Muslim countries